A comparative review of epinephrine and phenylephrine as vasoconstrictors in dental anesthesia: exploring the factors behind epinephrine's prevalence in the US - Deol, Navkiran; Alvarez, Gerardo; Elrabi, Omar; Chen, Gavin; Ferraro, Nalton (Journal of dental anesthesia and pain medicine: JDAPM, 2023)
This review paper delves into the comparative study of epinephrine and phenylephrine as vasoconstrictors in dental anesthesia, exploring their histories, pharmacological properties, and clinical applications. The study involved a comprehensive literature search, focusing on articles that directly compared the two agents in terms of efficacy, safety, and prevalence in dental anesthesia. Epinephrine, with its broad receptor profile, has been a predominant choice, slightly outperforming in the context of prolonging dental anesthesia and providing superior hemostasis, which is crucial for various dental procedures. However, the stimulation of beta-adrenergic receptors caused by epinephrine poses risks, especially to patients with cardiovascular conditions. Phenylephrine, a selective alpha-1 adrenergic agonist, emerges as a safer alternative for such patients, avoiding the cardiovascular risks associated with epinephrine. Moreover, its vasoconstrictive effect may not be as deleterious as that of epinephrine, due to its selective action. This review reveals that despite the potential benefits of phenylephrine, epinephrine continues to dominate in clinical settings, due to its historical familiarity, availability, and cost-effectiveness. The lack of commercially available pre-made phenylephrine dental carpules in most countries, except Brazil, and a knowledge gap within dental academia regarding phenylephrine, contribute to its limited use. This review concludes that while both agents are effective, the choice between them should be based on individual patient conditions, availability, and the practitioner's knowledge and familiarity with the agents. The underuse of other vasoconstrictors like levonordefrin and the unavailability of phenylephrine in pre-mixed dental cartridges in many countries highlights the need for further exploration and research in this field. Furthermore, we also delve into the role of levonordefrin and examine the rationale behind the exclusion of phenylephrine from commercially available pre-mixed local anesthetic carpules, suggesting a need for a responsive approach from pharmaceutical manufacturers to the distinct needs of the dental community.